2006
DOI: 10.1017/s0144686x06005320
|View full text |Cite
|
Sign up to set email alerts
|

Are different forms of care-management for older people in England associated with variations in case-mix, service use and care-managers' use of time?

Abstract: This paper reports one component of an evaluation of the different forms, types and models of local authority social services' care-management for older people that have emerged in England since 1993. It was undertaken at a time of a growing debate about whether care-management differentiated those with simple from complex needs, and whether for the latter a multi-disciplinary approach was required. A sample representative of different approaches to care-management was selected from a national survey of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Inthesecondstrand,informationwastakenfromtwonational postalsurveysofcarecoordinationarrangementsinEngland.The firstsurveywasrelatedtoLAcare management in older people's services and was derived from earlier studies (Challis, Darton, Hughes, Huxley, & Stewart, 1998;Challis, Hughes, Jacobs, Stewart, & Weiner, 2007;Weiner, Stewart, Hughes, Challis, & Darton, 2002). Questionnaires were distributed to all LAs in Englandin2006.Aresponserateof79%(118of149LAs)was achieved.ThesecondsurveywasrelatedtoPCTcase management for people with long-term conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Inthesecondstrand,informationwastakenfromtwonational postalsurveysofcarecoordinationarrangementsinEngland.The firstsurveywasrelatedtoLAcare management in older people's services and was derived from earlier studies (Challis, Darton, Hughes, Huxley, & Stewart, 1998;Challis, Hughes, Jacobs, Stewart, & Weiner, 2007;Weiner, Stewart, Hughes, Challis, & Darton, 2002). Questionnaires were distributed to all LAs in Englandin2006.Aresponserateof79%(118of149LAs)was achieved.ThesecondsurveywasrelatedtoPCTcase management for people with long-term conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Case files of consecutive referrals for care management from the 4 January 2000 or as soon as possible thereafter were included (Challis et al, 2007). This comprised the comparison or historical control group (Bowling, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of physical dependency was defined as scoring two or more on this scale. Case files were interrogated for evidence of mental health problems including problems with cognitive skills, communication, behaviour, and short-term memory as these are often associated with dementia in older people (Challis et al, 2007). Evidence of problems with cognitive skills (cognitive impairment) was thought to be the most appropriate proxy measure for evidence of a mental health problem.…”
Section: Methodsmentioning
confidence: 99%
“…Challis et al (2005) found that closer communication across the professions resulted generally in less time needing to be spent on care planning and case review in the minority of social services departments that have NHS staff working alongside social workers. Challis et al (2005) found that closer communication across the professions resulted generally in less time needing to be spent on care planning and case review in the minority of social services departments that have NHS staff working alongside social workers.…”
Section: Introductionmentioning
confidence: 99%